2014
DOI: 10.1071/ah12027
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admissions caused by adverse drug events: an Australian prospective study

Abstract: Objective. To assess the frequency of adverse drug event (ADE)-related admissions (ADE-RAs) during a prospective medical record review of patients admitted to a metropolitan tertiary referral hospital.Methods. Potential ADE-RA cases were identified by examination of case records of randomly selected patients. Cases were assessed by an expert panel to measure study outcomes, which were the frequency (ADEs and ADE-RAs) as well as type, likelihood of causality, severity, avoidability and detection of ADEs.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…[1][2][3][4] The term ADR is used here to refer to the causal connections between the proper use of medications and adverse events, excluding those due to medication errors. ADR are associated with potentially preventable morbidities and mortality, placing a substantial burden on the healthcare systems in Australia 5,6 as well as internationally. [2][3][4]7,8 Previous studies showed different patterns of ADR using routinely collected hospitalisation data.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The term ADR is used here to refer to the causal connections between the proper use of medications and adverse events, excluding those due to medication errors. ADR are associated with potentially preventable morbidities and mortality, placing a substantial burden on the healthcare systems in Australia 5,6 as well as internationally. [2][3][4]7,8 Previous studies showed different patterns of ADR using routinely collected hospitalisation data.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 50% of geriatric outpatients were considered at risk for DDIs in a study conducted in the Netherlands 13. In acute medical wards, the rate of potential DDIs is suggested to be as high as 60%,14 although actual confirmed ADR rates were 16% 15. In cancer care, potential DDI rates have been estimated to affect between 10% and 63% of patients 16–18…”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence of fatal ADRs can largely depend on the type of hospital or ward [9][10][11]. Drugs most frequently involved in fatal ADRs have been cytotoxic agents, antithrombotics and nonsteroidal anti-inflammatory drugs (NSAIDs) [3,9,[12][13][14][15][16][17].…”
mentioning
confidence: 99%